2022
DOI: 10.3389/fimmu.2022.1015529
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and directed inhibition of ECP production by human neutrophils

Abstract: BackgroundNeutrophils are involved in the pathophysiology of allergic asthma, where the Eosinophil Cationic Protein (ECP) is a critical inflammatory mediator. Although ECP production is attributed to eosinophils, we reported that ECP is also present in neutrophils from allergic patients where, in contrast to eosinophils, it is produced in an IgE-dependent manner. Given the key role of ECP in asthma, we investigated the molecular mechanisms involved in ECP production as well as the effects induced by agonists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
4
0
1
Order By: Relevance
“…Several studies have investigated the mechanism by which ECP induces IL-8, and the most widely accepted view is that ECP binds to the CD18 membrane protein on the surface of human cells, activating intracellular signaling pathways that lead to the release of various in ammatory mediators, including IL-8. [3] Speci cally, ECP may mediate IL-8 production through the following pathways:1Activation of the NF-κB pathway: ECP can activate the nuclear transcription factor-κB (NF-κB) pathway, thereby inducing the expression and secretion of IL-8. [4] 2 Activation of the MAPKs pathway: ECP can also activate the mitochondrial-associated protein kinases (MAPKs) pathway, which promotes the expression and secretion of IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the mechanism by which ECP induces IL-8, and the most widely accepted view is that ECP binds to the CD18 membrane protein on the surface of human cells, activating intracellular signaling pathways that lead to the release of various in ammatory mediators, including IL-8. [3] Speci cally, ECP may mediate IL-8 production through the following pathways:1Activation of the NF-κB pathway: ECP can activate the nuclear transcription factor-κB (NF-κB) pathway, thereby inducing the expression and secretion of IL-8. [4] 2 Activation of the MAPKs pathway: ECP can also activate the mitochondrial-associated protein kinases (MAPKs) pathway, which promotes the expression and secretion of IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is currently a lack of documented cases regarding the IgE-mediated generation of eosinophil cationic protein (ECP) in individuals suffering from allergic asthma. Furthermore, it has been noted that the administration of anti-interleukin-4 (IL-4) medication does not result in a reduction in eosinophil cationic protein (ECP) levels in the serum of these individuals [ 27 ]. Another study shows how in pediatric patients who have been diagnosed with asthma, the value of plasma eosinophil cationic protein (ECP) concentrations is a possible biomarker for measuring Type 2 inflammation, corticosteroid therapy response, and exacerbation outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Vega-Rioja et al ( 2022) demonstrated that human neutrophils may directly regulate and inhibit ECP production. Although eosinophils are thought to be the source of ECP, the authors discovered that ECP can also be found in the neutrophils of allergic patients, where it produces IgE-dependently [24].…”
Section: Immunological Mechanisms Of Ecpmentioning
confidence: 99%
“…Still, most importantly, FEV1 inversely correlates with the in vitro ECP secretion by peripheral neutrophils after an allergen challenge. The authors conclude that the in vitro production of neutrophil ECP could predict the severity of allergic asthma, and future strategies must consider the molecular pathways that offer potential therapeutic targets [24].…”
Section: Immunological Mechanisms Of Ecpmentioning
confidence: 99%